Mitochondrial dysfunction and therapeutic perspectives in osteoporosis - Liu, Jialing; Gao, Zhonghua; Liu, Xiangjie (Frontiers in Endocrinology, 2024)
Osteoporosis (OP) is a systemic skeletal disorder characterized by reduced bone mass and structural deterioration of bone tissue, resulting in heightened vulnerability to fractures due to increased bone fragility. This condition primarily arises from an imbalance between the processes of bone resorption and formation. Mitochondrial dysfunction has been reported to potentially constitute one of the most crucial mechanisms influencing the pathogenesis of osteoporosis. In essence, mitochondria play a crucial role in maintaining the delicate equilibrium between bone formation and resorption, thereby ensuring optimal skeletal health. Nevertheless, disruption of this delicate balance can arise as a consequence of mitochondrial dysfunction. In dysfunctional mitochondria, the mitochondrial electron transport chain (ETC) becomes uncoupled, resulting in reduced ATP synthesis and increased generation of reactive oxygen species (ROS). Reinforcement of mitochondrial dysfunction is further exacerbated by the accumulation of aberrant mitochondria. In this review, we investigated and analyzed the correlation between mitochondrial dysfunction, encompassing mitochondrial DNA (mtDNA) alterations, oxidative phosphorylation (OXPHOS) impairment, mitophagy dysregulation, defects in mitochondrial biogenesis and dynamics, as well as excessive ROS accumulation, with regards to OP ( Fig1 ) . Furthermore, we explore prospective strategies currently available for modulating mitochondria to ameliorate osteoporosis. Undoubtedly, certain therapeutic strategies still require further investigation to ensure their safety and efficacy as clinical treatments. However, from a mitochondrial perspective, the potential for establishing effective and safe therapeutic approaches for osteoporosis appears promising.